Dual symbiosis with co‐occurring sulfur‐oxidizing symbionts in vestimentiferan tubeworms from a Mediterranean hydrothermal vent. (2nd April 2014) - Zimmermann, Judith; Lott, Christian; Weber, Miriam; Ramette, Alban; Bright, Monika; Dubilier, Nicole; Petersen, Jillian M.
Summary Vestimentiferan Tws colonize hydrothermal vents and cold seeps worldwide. They lack a digestive system and gain nutrition from endosymbiotic sulfur‐oxidizing bacteria. It is currently assumed that vestimentiferan Tws harbour only a single endosymbiont type. A few studies found indications for additional symbionts, but conclusive evidence for a multiple symbiosis is still missing. We investigated Tws from Marsili Seamount, a hydrothermal vent in the Mediterranean Sea. Molecular and morphological analyses identified the Tws as Lamellibrachia anaximandri. 16S ribosomal RNA clone libraries revealed two distinct gammaproteobacterial phylotypes that were closely related to sequences from other Lamellibrachia symbionts. Catalysed reporter deposition fluorescence in situ hybridization with specific probes showed that these sequences are from two distinct symbionts. We also found two variants of key genes for sulfur oxidation and carbon fixation, suggesting that both symbiont types are autotrophic sulfur oxidizers. Our results therefore show that vestimentiferans can host multiple co‐occurring symbiont types. Statistical analyses of vestimentiferan symbiont diversity revealed that host genus, habitat type, water depth and geographic region together accounted for 27% of genetic diversity, but only water depth had a significant effect on its own. Phylogenetic analyses showed a clear grouping of sequences according to depth, thus confirming the important role water depth played in shaping vestimentiferan symbiont diversity.